A Study of Presupposition and Conversational Implicatures in the Comic Strip of “The Diary of a Wimpy Kid” - Helena Verusha Ali; Dini Hidayati; Yanuarius Yanu Dharmawan (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
This study aims at exploring the application of presupposition and conversational implicature in communication within comic strips from pragmatics field of study as proposed by Yule, (2006). The research design of this study is a qualitative design. The data were utterances and sentences in "The Diary of a Wimpy Kid" comic strip. This study reveals that there were four types of presuppositions implemented by the characters in “The Diary of A Wimpy Kid” comic, namely counter-factual presupposition, existential presupposition, factive presupposition, and lexical presupposition. Additionally, the research revealed that the characters in the comic employ two distinct forms of conversational implicatures: generalized conversational implicatures and particularized conversational implicatures.